143 Baltimore's underground gun market: availability of and access to guns. (5th May 2020) - Crifasi, Cassandra; Buggs, Shani; Booty, Marisa; Webster, Daniel; McAdams, Rebecca
Abstract : Statement of Purpose: Underground gun markets create opportunities for individuals who are prohibited from gun ownership to gain access to them. Understanding how these individuals obtain guns, as well as their unsuccessful attempts to get guns, is key to developing interventions that effectively restrict the supply of guns in an underground market. Methods/Approach: We recruited 195 men outside of parole and probation centers in Baltimore City. We conducted surveys with these criminal justice system-involved men about their experiences in the underground gun market. The survey data was gathered using an audio-assisted computer survey instrument. The survey was composed of questions about ability to acquire firearms, why they were desired, and selling/trading behaviors. Results: 30% of respondents (n=58) reported having experience in the underground gun market. More than half of these individuals were unsuccessful in their most recent attempt to obtain a firearm due to cost- or source-related barriers. Over 80% of individuals who did not already have access to a gun but wanted one (31/38) reported wanting to acquire one for safety or protection. Most respondents who had access to firearms had handguns (90%). Individuals reported selling or trading a gun (n=35) for money (69%), drugs (46%), or other guns (23%), or accepting guns as payment for drugs. Conclusions: Although an underground market can facilitate access to firearms, barriers exist that can prevent acquisition by high risk individuals. Significance and Contributions to Injury and Violence Prevention Science: This is the first study to understand the availability of and access to guns in Baltimore' underground gun market. Efforts should focus on strategies that increase accountability and restrict the supply of guns in an underground market or those that provide alternatives to gun carrying to feel safe.